Winter Record of the Pallid Harrier on the Sal River, Rostov Region, Russia - Ksenia S. Kuzmina (Пернатые хищники и их охрана)
This short report provides information about the first winter record of the Pallid Harrier (Circus macrourus) in the Rostov region.